Analysis of clinical trials of new drugs in China as of 2019. Issue 12 (December 2020) - Lin, Longfei; Chen, Yiren; Yan, Lei; Liu, Yuling; Ni, Jian; Yang, Hongjun; Li, Hui
Highlights: Clinical trials of drug research and development approved by NMPA. A total of 9, 401 clinical trials were analyzed in this article. Analyzed the phase, indication, dosage form, applicant of the clinical trials. Analyzed the status and provided proposal for drug R&D in China. Abstract : The research and development (R&D) of new drugs indicates scientific progress and economic development. However, little is known regarding ongoing or recent clinical trials in China. We analyzed data from clinical trials published before December 31, 2019, and found that the annual registration numbers are increasing annually in the country. Based on clinical indications, most tested drugs target cancers, nervous system, infections, and the cardiovascular system. Furthermore, clinical trials are mostly concentrated in Beijing, Shanghai, and Jiangsu, and conducted by large pharmaceutical companies, with multiple trials for several generic drugs. Going forward, it will be necessary to promote R&D in China of clinically relevant innovative drugs, drug delivery systems, and novel traditional Chinese medicine (TCM) and biological products, as well as to have a balanced distribution of clinical trials to sustainably meet public health needs.